E2F1 controls germ cell apoptosis during the first wave of spermatogenesis. (September 2015) - Rotgers, E.; Nurmio, M.; Pietilä, E.; Cisneros‐Montalvo, S.; Toppari, J.
Summary Cell cycle control during spermatogenesis is a highly complex process owing to the control of the mitotic expansion of the spermatogonial cell population and following meiosis, induction of DNA breaks during meiosis and the high levels of physiological germ‐cell apoptosis. We set out to study how E2F1, a key controller of cell cycle, apoptosis, and DNA damage responses, functions in the developing and adult testis. We first analyzed the expression pattern of E2f1 during post‐natal testis development using RNA in situ hybridization, which showed a differential expression pattern of E2f1 in the adult and juvenile mouse testes. To study the function of E2f1, we took advantage of the E2F1−/− mouse line, which was back‐crossed to C57Bl/6J genetic background. E2f1 loss led to a severe progressive testicular atrophy beginning at the age of 20 days. Spermatogonial apoptosis during the first wave of spermatogenesis was decreased. However, already in the first wave of spermatogenesis an extensive apoptosis of spermatocytes was observed. In the adult E2F1−/− testes, the atrophy due to loss of spermatocytes was further exacerbated by loss of spermatogonial stem cells. Surprisingly, only subtle changes in global gene expression array profiling were observed in E2F1−/− testis at PND20. To dissect the changes in each testicular cell type, an additional comparative analysis of the array data was performed making use of previously published data on transcriptomes of the individual testicular cell types. Taken together, our data indicate that E2F1 has a differential role during first wave of spermatogenesis and in the adult testis, which emphasizes the complex nature of cell cycle control in the developing testis.